Impact of Etanercept on Work and Activity Impairment in Employed Moderate to Severe Rheumatoid Arthritis Patients in the United States. Issue 10 (24th September 2013) - Hone, Devon; Cheng, Annie; Watson, Crystal; Huang, Baisong; Bitman, Bojena; Huang, Xing‐Yue; Gandra, Shravanthi R.
<x xml:space="preserve">Abstract</x> Objective To quantify the impact of etanercept on work and activity impairment in employed US patients with moderate to severe rheumatoid arthritis (RA). Methods This prospective, observational, longitudinal study recruited RA patients initiating etanercept (50 mg/week) between January 2009 and March 2010. The Work Productivity and Activity Impairment Questionnaire (WPAI) and domestic productivity questionnaire were administered by telephone interviews at baseline and at 1, 2, 3, and 6 months after etanercept initiation. The human capital approach was used to estimate the costs of work impairment. Changes in WPAI measures were analyzed using Wilcoxon's signed rank test. Results RA patients (n = 204) initiating etanercept were a mean ± SD age of 46.6 ± 10.9 years and 72% were women. After 6 months, 153 patients continued treatment (continuers) and showed significant decreases in overall work impairment (41.9% at baseline versus 25.2% at 6 months; P < 0.0001), absenteeism (8.4% versus 2.3%; P = 0.0001), presenteeism (38.9% versus 24.3%; P < 0.0001), and activity impairment (55.7% versus 30.9%; P < 0.0001) and a 76.4% reduction in work hours lost weekly due to RA (3.2 versus 0.8; P = 0.0001). The projected 12‐month gain in work productivity for continuers was 284.5 hours per patient, equating to $3, 233–22, 533 depending on annual income level, which partially or completely offset the annual cost of etanercept ($20, 190). Domestic productivity improved from 41.5% at baseline to 69.6% at 6 months (P < 0.0001). Conclusion In US employed moderate to severe RA patients, etanercept led to significant reductions in overall work and activity impairment; the value of increased work productivity partially or completely offset the cost of treatment.